An Integrated Approach of Yoga and Naturopathy in the Management of Post-Traumatic Stroke - A Case Report - Jaheer Hussain, A; Venkateswari, K; Rithaniya, S; Prashanth, S (Indian Journal of Integrative Medicine, 2024)
The World Health Organization defines stroke as a sudden onset of focal or global disturbance of cerebral function, lasting 24 hours or resulting in death, with vascular origin. In India, population-based studies show stroke prevalence rates range from 84 to 262 per 100,000 in rural areas and 334 to 424 per 100,000 in urban areas. Complementary and alternative medicine (CAM) modalities like Yoga and Naturopathy have the potential to manage musculoskeletal conditions. These approaches are drugless and employ minimally invasive or non-invasive methods to enact modifications within the body, thereby aiding in the process of recovery. A 23-year-old patient came to the Outpatient department on January 10, 2022; with a known case of stroke in the past 6 months. An Integrated Yoga and Naturopathy intervention has been given for 4 months. The patient was assessed pre and post-data for the study taking data on Body Mass index (BMI), Fugl Meyer Assessment (FMA), Modified Birth Index (MBI), Berg Balance Scale (BBS), and QOL SF-12, and results show that after 4 months yoga and naturopathy intervention like yoga, acupuncture, and hydrotherapy there was considerable change in FMS from 48 to 92 and MBI scale from 60 to 90 and BBS from 38 to 56 and QOL SF-12: from 73 to 98.83. The results suggest that Yoga and Naturopathy interventions are likely to play a role in rehabilitation of the stroke patients.